THE TRADITION OF HASHAR AND RELATED OBLIGATIONS IN THE PERIOD OF THE UZBEK KHANATES - Ulugbek Kuchkarovich Ismoilov (Journals Park Publishing, 2025)
This article provides information about the types of forced labor used in practice in connection with agricultural work in the Turkestan region during the Uzbek khanates - shoemaking, hashar, etc. In particular, the conditions of shoemaking, factors calling for hashar, conditions and methods of organizing hashar are discussed in more detail.
Keywords: Shoemaking, hashar, barshina, Land-mosque, bonded labor, forced labor, labor obligations, notes.